40 Terrorism Databases and Data Sets: a New Inventory - Bowie, Neil G. (Perspectives on terrorism, 2021)
This Research Note is a follow up from three previously published Research Notes by the author in this journal titled: ‘Terrorism Events Data: An Inventory of Databases and Data Sets, 1968-2017’[URL: http://www.terrorismanalysts.com/pt/index.php/pot/article/view/622/1226 ], ‘30 Terrorism Databases and Data Sets: a New Inventory’[URL: http://universiteitleiden.nl/binaries/content/assets/customsites/perspectives-on-terrorism/2018/issue-5/bowie.pdf ] and ‘A New Inventory of 30 Terrorism Databases and Data Sets’ [URL: https://www.universiteitleiden. nl/binaries/content/assets/customsites/perspectives-on-terrorism/2020/issue-1/bowie.pdf]. Together, the previous inventories covered 120 databases and data sets. This Research Note describes 40 more databases and data sets in the same three categories: i. Academic, Think Tank and Independent Databases (n =32) ii. Commercial Databases (n =2) and iii. Governmental Databases (n =6). Most of these data refer to terrorism, yet a few are broader, covering other forms of political violence as well as armed conflicts.